2002
DOI: 10.1002/dvdy.10153
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of anti‐Müllerian hormone expression, as related to DMRT1, SF‐1, WT1, GATA‐4, Wnt‐4, and Lhx9 expression, in the chick differentiating gonads

Abstract: In mammals, anti-Mü llerian hormone (AMH) is produced by Sertoli cells from the onset of testicular differentiation and by granulosa cells after birth. In birds, AMH starts to be expressed in indifferent gonads of both sexes at a similar level and is later upregulated in males. We previously demonstrated that, unlike in mammals, the onset of AMH expression occurs in chick embryo in the absence of SOX9. We looked for potential factors that might be involved in regulating AMH expression at different stages of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 62 publications
(77 reference statements)
8
106
1
Order By: Relevance
“…These investigations revealed that cFoxL2 protein distribution was restricted to the medullar part of the ovary during early development. The same region of expression has been reported for aromatase transcripts Nakabayashi et al, 1998;Nishikimi et al, 2000;Oreal et al, 2002) and for the aromatase protein (Smith et al, 2003). The double immunolocalization of cFoxL2 and aromatase proteins to the sections of the left female gonad at E14 in our study demonstrated that cFoxL2 and aromatase proteins are expressed in the same cells.…”
Section: Foxl2 and Ovarian Differentiation In Chickensupporting
confidence: 87%
See 3 more Smart Citations
“…These investigations revealed that cFoxL2 protein distribution was restricted to the medullar part of the ovary during early development. The same region of expression has been reported for aromatase transcripts Nakabayashi et al, 1998;Nishikimi et al, 2000;Oreal et al, 2002) and for the aromatase protein (Smith et al, 2003). The double immunolocalization of cFoxL2 and aromatase proteins to the sections of the left female gonad at E14 in our study demonstrated that cFoxL2 and aromatase proteins are expressed in the same cells.…”
Section: Foxl2 and Ovarian Differentiation In Chickensupporting
confidence: 87%
“…Two other transcriptional factors (Wnt4 and DAX1), which are considered to be suppressive factors of the male pathway in mammalian sex differentiation, do not seem to play the same role in the chicken. WNT4 expression in chickens is not dimorphic as in mammals during gonad differentiation (Oreal et al, 2002), and DAX1 is only slightly up-regulated in female compared with male differentiating gonads (Smith et al, 1999).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In trout, both amh and sox9a2 were detected in female embryonic gonads by ISH, despite a higher level of expression in the differentiating testis. Such an incomplete sexually dimorphic expression pattern has already been described for sox9 genes in some fish (Zhou et al, 2003;Nakamoto et al, 2005), and for Amh in birds (Oreal et al, 1998(Oreal et al, , 2002. In trout, it is currently difficult to draw any conclusions about the implication of sox9 genes as we were unable to investigate the cellular localization of sox9a1 by ISH, but its temporal expression profile seems to be sexually dimorphic earlier than those of sox9a2 and amh.…”
Section: Figmentioning
confidence: 75%